Human Primary Monocytes as a Model for in vitro Immunotoxicity Testing: Evaluation of the Regulatory Properties of TiO2 Nanoparticles - Svadlakova, Tereza; Kolackova, Martina; Kulich, Pavel; Kotoucek, Jan; Rosecka, Michaela; Krejsek, Jan; Fiala, Zdeněk; Andrýs, Ctirad (International journal of nanomedicine, 2025)
INTRODUCTION: A critical step preceding the potential biomedical application of nanoparticles is the evaluation of their immunomodulatory effects. Such nanoparticles are expected to enter the bloodstream where they can be recognized and processed by circulating monocytes. Despite the required biocompatibility, this interaction can affect intracellular homeostasis and modulate physiological functions, particularly inflammation. This study focuses on titanium dioxide (TiO2) as an example of relatively low cytotoxic nanoparticles with potential biomedical use and aims to evaluate their possible modulatory effects on the inflammasome-based response in human primary monocytes. METHODS: Monocyte viability, phenotypic changes, and cytokine production were determined after exposure to TiO2 (diameter, 25 nm; P25) alone. In the case of the modulatory effects, we focused on NLRP3 activation. The production of IL-1β and IL-10 was evaluated after (a) simultaneous activation of monocytes with bacterial stimuli muramyl dipeptide (MDP), or lipopolysaccharide (LPS), and TiO2 (co-exposure model), (b) prior activation with TiO2 alone and subsequent exposure to bacterial stimuli MDP or LPS. The differentiation of TiO2-treated monocytes into macrophages and their polarization were also assessed. RESULTS: The selected TiO2 concentration range (30-120 µg/mL) did not induce any significant cytotoxic effects. The highest dose of TiO2 promoted monocyte survival and differentiation into macrophages, with the M2 subset being the most prevalent. Nanoparticles alone did not induce substantial production of inflammatory cytokines IL-1β, IL-6, or TNF-α. The immunomodulatory effect on NLRP3 depended on the type of costimulant used. While co-exposure of monocytes to MDP and TiO2 boosted NLRP3 activity, co-exposure to LPS and TiO2 inhibited NLRP3 by enhancing IL-10 release. The inhibitory effect of TiO2 on NLRP3 based on the promotion of IL-10 was confirmed in a post-exposure model for both costimulants. CONCLUSION: This study confirmed a non-negligible modulatory effect on primary monocytes in their inflammasome-based response and differentiation ability.
Keywords: buněčná diferenciace; Metal Nanoparticles; monocytes; Monocytes; testy toxicity; Toxicity Tests; protein NLRP3; Cell Differentiation; Titanium; interleukin-10; Humans; Cells, Cultured; nanočástice; acetylmuramyl-alanyl-isoglutamin; lidé; Interleukin-1beta; monocyty; NLRP3; Lipopolysaccharides; titan; interleukin-1beta; inflamasomy; kovové nanočástice; Interleukin-10; TiO2 nanoparticles; Inflammasomes; immunomodulation; polarization; lipopolysacharidy; viabilita buněk; macrophages; Cytokines; Macrophages; Acetylmuramyl-Alanyl-Isoglutamine; kultivované buňky; cytokiny; Nanoparticles; Cell Survival; NLR Family, Pyrin Domain-Containing 3 Protein; makrofágy